Pengaruh Model Pembelajaran Think Talk Write Terhadap Kemampuan Menulis Siswa Kelas XI SMAN 1 Pedes Tahun Ajaran 2023/2024 - Amelia, Kezia Christabel; Nuraini, Cut; Meliasanti, Ferina (Jurnal Ilmiah Wahana Pendidikan, 2024)
This aims of this research to explain the diference learning result of the ability of writing explanation text with Think Talk Write learning model in XI senior high school of SMAN 1 Pedes Karawang, in academic year 2023/2024. This research is using quantitative experimental methods. The expected goal of this research is to determine the effect of implementing the think talk write learning model in writing explanatory texts which is applied in class XI of SMAN 1 Pedes in the 2023/2024 academic year. The sampling technique in this research used a non-random sampling technique. The population in this study was all students in class XI for the 2023/2024 academic year. However, the samples used were classes XI MIPA 5 and XI MIPA 6. Based on the results of the hypothesis test carried out, it is known that the Sig. (2-tailed) obtained is 0.030. So it can be concluded that the application of the think talk write learning model applied to the experimental class is more effective when compared to the conventional learning model applied to the control class.